Investigating Language and Culture Awareness of Pre-Service Science Teachers in Ireland - Ebru Eren; Catherine Martin (MDPI AG, 2024)
Irish classrooms are becoming increasingly diverse across all levels of education due to the sustained inward migration of non-nationals to Ireland. These demographic changes have enriched the linguistic and cultural fabric of Irish society, including the educational landscape of Ireland. However, in addition to the value such diversity brings to Irish classrooms, there exist many challenges as the Irish education system needs to continue to adapt to develop more inclusive and language- and culture-sensitive pedagogical approaches. One of the ways in which the Irish educational system can respond to this challenge is through the adaptation of its pre-service science teacher education programmes to prepare teachers to teach in linguistically and culturally diverse classrooms. Therefore, it is important to investigate the needs of pre-service science teachers to inform updates to existing teacher education programmes to prepare future science teachers to meet this challenge. Consequently, this study has attempted to capture the perceptions, knowledge and attitudes of current pre-service teachers regarding the role of language and culture in science teaching, awareness of the needs of students whose first language is not English or Irish and teachers' knowledge of pedagogical strategies to develop language- and culture-sensitive science teaching approaches. Here, we report data from a survey of pre-service science teachers undertaking science teacher training at Irish universities at the undergraduate and postgraduate levels. The data highlight gaps in trainee teachers' language awareness and their lack of pedagogical knowledge in dealing with language and cultural diversity in science classrooms. Implications for the future development of pre-service science teacher education programmes are discussed.